Fluorescent two‐photon nanolithography - Kunik, Dario (2008)
Improving the excitation conditions in two-photon fluorescent lithography reduces the size of the fabricated structures to nanometre scales.We demonstrate that a precise control of the illumination profile and the scanning speed of the laserbeamis enough to decrease the photo-polymerization volume of resins by orders of magnitude. This work also shows experimental evidence of surface effects that yield a different polymerization intensity threshold compared with bulk. Such phenomenon enables to perform a non-linear optical nanolithography in a simple way, allowing fast-prototyping procedures. We present a detailed study of the polymer growth process using fluorescence and atomic force microscopy.